(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The purpose of this presentation is to raise some reflections on the influence of the economic argument on the analysis of legal claims, its repercussions on legal reasoning and the review of public policies, through the necessary intertwining of economics and law. The epistemological option outlined in this paper is to analyze the influence of economics on law, precisely in order to approach the issue from a macro analysis of the phenomenon, but with a legal interpretation bias - without detracting from the magnitude of economics in the realization of law. The article seeks to scale up the different discussions held in the lectures of the Constitutional Law Course “Limits and Possibilities of Jurisdictional Activity in Brazilian Constitutionalism”, held at the School of Magistrates of the TRF of the 3rd Region, in May 2013, emphasizing the economic argument in court, situating the issue within constitutional interpretation. The essay thus seeks to express the major concerns raised by the economic factual symbiosis between legal institutes and their application in market society; the need to understand them in a macro social context; and to point out the repercussions of the result of this often necessary symbiosis between Law and Economics in order to assess the functionality of the system in relation to the constitutional guidelines of the Democratic Rule of Law.